A COMPARATIVE SEMANTIC STUDY OF THE CONCEPTS OF HEAVEN AND EARTH (Scientific journal of the Fergana State University, 2023)
In the article, the expressions and proverbs involving the concepts of "Heaven", "Earth" are comparatively studied, the specific meanings of the culture and worldview reflecting the national views, the similarities in the mentality and life principles of the two languages, and general conclusions about the differences are drawn using examples of the content used in the contexts.